2021
DOI: 10.1111/ajco.13578
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of docetaxel‐associated febrile neutropenia with primary granulocyte colony‐stimulating factor in Chinese metastatic hormone‐sensitive and castration‐resistant prostate cancer patients

Abstract: IntroductionAsian prostate cancer (PC) patients are particularly susceptible to docetaxel‐related febrile neutropenia (FN). We evaluated primary granulocyte colony‐stimulating factor (GCSF) for preventing FN in Chinese patients with metastatic hormone‐sensitive PC (mHSPC) and castration‐resistant PC (mCRPC).Patients and MethodsData from two cohorts of 377 Chinese patients with mHSPC (100; 26.5%) and mCRPC (277; 73.5%) treated with docetaxel at six public oncology centres were analysed with multivariate regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 29 publications
3
12
1
Order By: Relevance
“…In addition, we found that poor PS is an independent risk factor of FN, in line with a recent study from Asia 31 . In general, such comorbid patients are expected to have a high incidence of chemotherapy‐induced AEs 32 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In addition, we found that poor PS is an independent risk factor of FN, in line with a recent study from Asia 31 . In general, such comorbid patients are expected to have a high incidence of chemotherapy‐induced AEs 32 .…”
Section: Discussionsupporting
confidence: 90%
“…Finally, the incidence rates of FN, as well as neutropenia in our study, were higher compared with the previous literature 3,7,20,21 . The high incidence rates of neutropenia and FN have been noted in Asian patients 27,31,35,36 . Thus, the generalizability of our results to non‐Asian patients is limited.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…On behalf of the Hong Kong Society of Uro-Oncology (HKSUO), our team reviewed the incidence of docetaxel-related haematological toxicities in mPC patients treated in six public oncology centres in Hong Kong [ 50 ]. Among 377 Chinese patients who received docetaxel, the overall incidence of FN was 15%; those with mCRPC had a higher incidence (17%) compared with that in the mHSPC patients (12%).…”
Section: Risk Management Of Taxane-related Myelosuppression In Asian Pc Patientsmentioning
confidence: 99%